2013
DOI: 10.1039/c3cc44342f
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional zeolitic imidazolate framework with a cushion-shaped cavity for CO2 adsorption

Abstract: A new two-dimensional zeolitic imidazolate framework (named as ZIF-L) was synthesized in zinc salt and 2-methylimidazole (Hmim) aqueous solution at room temperature. ZIF-L (Zn(mim)2·(Hmim)1/2·(H2O)3/2 or C10H16N5O3/2Zn) has unique cushion-shaped cavities and leaf-like crystal morphology, and exhibits excellent CO2 adsorption properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
466
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 581 publications
(517 citation statements)
references
References 23 publications
46
466
2
3
Order By: Relevance
“…Typically, 0.863 g of Zn(OAc) 2 and 11.350 g 2-Hmim were first dissolved in 8 mL and 80 mL deionized water, respectively. The two solutions were then mixed under stirring at room temperature for 8 h. Leaf-shaped ZIFs was synthesized following the literature [18]. 0.59 g of Zn(NO 3 ) 2 ·6H 2 O and 1.30 g of 2-Hmim were dissolved in 40 mL deionized water, respectively.…”
Section: Zifs Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, 0.863 g of Zn(OAc) 2 and 11.350 g 2-Hmim were first dissolved in 8 mL and 80 mL deionized water, respectively. The two solutions were then mixed under stirring at room temperature for 8 h. Leaf-shaped ZIFs was synthesized following the literature [18]. 0.59 g of Zn(NO 3 ) 2 ·6H 2 O and 1.30 g of 2-Hmim were dissolved in 40 mL deionized water, respectively.…”
Section: Zifs Synthesismentioning
confidence: 99%
“…He et al [17] developed a novel method to produce ZIF-8 with a cubic-at a stoichiometric metal and ligand molar ratio of 1:2 in the presence of ammonium hydroxide. Chen et al [18] reported a two-dimensional with a leaf-shaped morphology at the 2-Hmim and Zn molar ratio of 8 in water. Previous studies has reported that the morphology of the adsorbents may have significant impact on the adsorption behavior [19], while few attention had been drawn on the impact of the morphology of ZIFs on their adsorption performance in water treatment [20].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of ZIF-L followed a typical process as recently reported [27]. Equal volumes (40 mL) of zinc nitrate hexahydrate (14.7 g/L) and Hmim (32.5 g/L) were dissolved in water and stirred at room temperature for 4 h. The product was collected by centrifugation (8000 rpm, 20 min) and rinsed with methanol.…”
Section: Synthesis Of Zif-lmentioning
confidence: 99%
“…The same zinic salt and 2-methylimidazole are commonly used to synthesize ZIF-8. Both zinc/2-methylimidazole ratio and the use of water as solvent are the key to synthesis of ZIF-L. ZIF-L is a unique 2-dimensional ZIF which has a semi-SOD topology and leaf-like morphology [27]. The aim of this work was to investigate the effect of the two-dimensional ZIF-L nanoflakes on the phase inversion process which influences the overall membrane morphology and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Undoped ZIF-8 crystals were synthesized as reported before (16 Undoped ZIF-L crystals were synthesized as described elsewhere (5,6). Aqueous (50 mL) solutions of Zn(NO3)2.6H2O (0.662 g) and Hmim (1.642 g) were mixed by the dropwise addition of the Zn …”
Section: Synthesis Of Undoped/doped Zif 8 and Zif-l Crystalsmentioning
confidence: 99%